ANALISIS PERBAIKAN TANAH LEMPUNG LUNAK MENGGUNAKAN GEOTEXTILE (STUDY KASUS PEMBANGUNAN JALAN LINGKAR TUBAN STA 9+050 – 9+075) - Matnor Aripindi; Laily Endah Fatmawati; Herry Widhiarto (LPPM Universitas Bina Bangsa, 2022)
Soil is a material that has a significant influence on the performance of building construction. Soil improvement techniques are soil stabilization measures by improving the characteristics of the original soil, to meet the technical requirements required by the construction, such as increasing the bearing capacity and shear strength of the soil, reducing soil compressibility, increasing or decreasing soil permeability, and so on. In the Tuban Ring Road Development Project, there are soft clay soils at STA 9+050 – 9+075, where the subsidence was seen after placing selected embankments 30 cm thick. The analysis used in this study uses the geotextile method as an alternative to reinforcement at STA 9+050 – 9+075 in the Tuban Ring Road Development project. From the data obtained it is known that the soil appears to be soft soil. The type of geotextile used is UW-250 with a strength capacity of 5.20 t/m which serves as a separator for the reinforcement of the Tuban Ring Road Development Project at STA 9+050 – 9+075. Based on the data analysis performed, it can be concluded that the amount of settlement that occurs due to loads on soft soil at STA 9+050 – 9+075 is 57.35 cm and the consolidation time obtained is 190.311 years. The length of the geotextile (L) planted at STA 9+050 – 9+075 in the Tuban Ring Road Development project is 9.884 m installed in 1 layer. The value of Safety Factor (SF) on soil with selected embankments and geotextile reinforcement at STA 9+050 – 9+075 is 2.7, so it is known that the use of geotextile as an alternative to soft soil improvement at STA 9+050 – 9+075 in development projects Tuban Ring Road.